Cost system for the third sector: a study of a long-stay institution for older adults in the Alto Vale do Itajaí (SC) (Revista Brasileira de Contabilidade e Gestão, 2012)
Every manager needs data and information on the activities of the entity, regardless of branch of activity. In nonprofits the importance of data and information is even greater for management due to scarce resources and dependence on aid, whether through financial donations or volunteer work. To know what data and information, especially related to costs, a study in an institution of Long Term Elderly - ILPI Upper Valley Itajai - SC. The study aimed to identify the costs for each guest, the entity has to provide its services. Was used for data collection, exploratory research through a case study, a qualitative and quantitative approach. With data collection, performed through documents and unstructured interviews, gave the survey to allocate spending in each department and then highlight the cost of each guest. The survey was conducted during the first four months of 2011 and were able to identify the costs of guests ranged from R $ 1,204.00 to R $ 1,713.50 according to the degree of dependence, following criteria set by ANVISA.
Keywords: management of third sector; accounting; costs